2009
DOI: 10.1182/asheducation-2009.1.313
|View full text |Cite
|
Sign up to set email alerts
|

Supplements for immune enhancement in hematologic malignancies

Abstract: This brief review aims to discuss the various cellular immunological aspects and related mechanisms of the use of specific components from traditional herbal medicines. We begin with lessons learned from thalidomide as an effective single drug with multiple mechanisms of action to treat multiple myeloma. Examples of "supplements" or integrative therapy will be drawn from arsenic trioxide, medicinal mushrooms including Coriolus vesicular and Ganoderma lucidum, followed by the discussion of beta-glucans affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 41 publications
0
22
0
1
Order By: Relevance
“…Preclinical data show good evidence for a beneficial effect of b-glucan in cancer [38][39][40]; however, there is some debate about whether these effects are due to direct cytotoxic effects or immunomodulatory mechanisms [41,42]. For example, Yoon et al reported that b-glucan purified from mutated S. cerevisiae inhibited lung metastasis of colon 26-M3.1 carcinoma that was associated with splenocyte proliferation, tumoricidal activity of peritoneal macrophages, and NK cell cytotoxicity but there was no effect of this treatment on direct cytotoxicty of colon 26-M3.1 cells in vitro [43].…”
Section: B-glucan and Cancermentioning
confidence: 99%
“…Preclinical data show good evidence for a beneficial effect of b-glucan in cancer [38][39][40]; however, there is some debate about whether these effects are due to direct cytotoxic effects or immunomodulatory mechanisms [41,42]. For example, Yoon et al reported that b-glucan purified from mutated S. cerevisiae inhibited lung metastasis of colon 26-M3.1 carcinoma that was associated with splenocyte proliferation, tumoricidal activity of peritoneal macrophages, and NK cell cytotoxicity but there was no effect of this treatment on direct cytotoxicty of colon 26-M3.1 cells in vitro [43].…”
Section: B-glucan and Cancermentioning
confidence: 99%
“…One of the major functions of TCM is as an immune modulator [27,28]. Polysaccharides from TCM have been reported to work efficiently as immune modulators in improving both cellular and humoral immunity [7,13,15,19,25], immune functions of the immunosuppressive mice, modulating secretion of cytokines and other situations of immune dysfunction in the human body [2,5,8,9,30], especially in restoring immune system of cancer patients, whose immune system was damaged severely by chemotherapy or radio-therapy [16,26,28]. Achyranthes bidentata has long been prescribed to prevent and treat various human diseases, particularly in China, Japan, and Korea.…”
Section: Introductionmentioning
confidence: 99%
“…In our Case 3, the only patient who continued GLS for a long period, CA72-4 surged rapidly when GLS was initiated and then sharply decreased, as did CEA, without any change in treatment, thus mirroring the aforementioned studies. Taking into consideration that studies demonstrate that the GLS extract possesses direct cytotoxic effects on cancer cells through multiple mechanisms such as apoptosis, cell cycle arrest, and enhanced cell-mediated immune response, [37][38][39][40] there is a possibility that the surge of CA72-4 might be due to GLS-produced tumor cell lysis. However, evidence to support this hypothesis is lacking as no other clinical symptom improvements accompanied the CA72-4 surge.…”
mentioning
confidence: 99%